Study on the Mercury Migration in Clinker-Producing. Issue 1 (1st January 2022) - Li, Lingmei; Wang, Zhaojia; Cui, Suping; Yang, Feihua; Zhu, Yanchen; Li, Yinming
Abstract: Mercury is one most important global pollutants in the environment. The article studied the mercury migration according to the mercury migration in the cement process, in which a model for the relationship between the mercury input, internal circulation and output is built. In the model, mercury concentration in each stage of the process was calculated and characterized with different input, which were Consistent with actual verification, and then the reasonable method was advised to prevent the mercury pollution. The simulation showed that the mercury input is below 0.1g/t.cli, and the mercury gas emission concentration is below 0.05 mg/Nm 3 whenever the mode of raw mill is on or off. But once the mercury input is over 0.23 g/t.cli, the mercury gas emission concentration is over 0.05mg/Nm 3 although the mode of raw mill is on. The mercury content in ERM and KA is almost ten times higher than raw material, and the mercury content in KA is almost ten times higher than raw meal extraction, and multiples increase with higher mercury input as well. Even if mercury is continuously enriched internal, there is no limit of mercury concentration saturation.